2018
DOI: 10.1080/02640414.2018.1504602
|View full text |Cite
|
Sign up to set email alerts
|

Application of the principal component waveform analysis to identify improvements in vertical jump performance

Abstract: The purpose of this study was to determine the effects of training on the force-, velocity-, and displacement-time curves using principal component analysis (PCA) to examine the pre to post intervention changes. Thirty-four trained women basketball players were randomly divided into training and control groups. The training intervention consisted of full squats combined with repeated jumps. The effects of the intervention were analysed before and after the training period of 6 weeks by comparing the principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…After study titles and abstracts were screened, a further 2172 studies were removed. Accordingly, full-text versions of 498 studies were screened, with 32 studies 28 , 29 , 30 , 42 , 43 , 44 , 45 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 considered eligible for meta-analysis. The included studies involved 442 participants in 37 experimental groups and 376 participants in 32 control groups.…”
Section: Resultsmentioning
confidence: 99%
“…After study titles and abstracts were screened, a further 2172 studies were removed. Accordingly, full-text versions of 498 studies were screened, with 32 studies 28 , 29 , 30 , 42 , 43 , 44 , 45 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 considered eligible for meta-analysis. The included studies involved 442 participants in 37 experimental groups and 376 participants in 32 control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Functional Principal Component Analysis (FPCA) has been applied to a diverse range of applications in biomechanics. Studies have reported strong associations between FPCs and various performance or injury risk measures in sports, including rowing, swimming, weightlifting, race walking and jumping [41,[43][44][45][46][47][48][49][50][51]. These applications analysed the FPC scores using descriptive statistics, t-tests, ANOVA, discriminant analysis or a simple regression model to address their research questions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Functional Principal Component Analysis (FPCA) has been applied to a diverse range of applications in biomechanics. Studies have reported strong associations between FPCs and various performance or injury risk measures in sports, including rowing, swimming, weightlifting, race walking and jumping [37,[39][40][41][42][43][44][45][46][47]. These applications analysed the FPC scores using descriptive statistics, t-tests, ANOVA, discriminant analysis or a simple regression model to address their research questions.…”
Section: Introductionmentioning
confidence: 99%